Drug Discovery Based on Fluorine-Containing Glycomimetics - Wei, Xingxing; Wang, Pengyu; Liu, Fen; Ye, Xinshan; Xiong, Decai (Molecules (Basel, Switzerland), 2023)
Glycomimetics, which are synthetic molecules designed to mimic the structures and functions of natural carbohydrates, have been developed to overcome the limitations associated with natural carbohydrates. The fluorination of carbohydrates has emerged as a promising solution to dramatically enhance the metabolic stability, bioavailability, and protein-binding affinity of natural carbohydrates. In this review, the fluorination methods used to prepare the fluorinated carbohydrates, the effects of fluorination on the physical, chemical, and biological characteristics of natural sugars, and the biological activities of fluorinated sugars are presented.